2014
DOI: 10.4314/bcse.v28i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Heteropolyacides as green and reusable catalysts for the synthesis of [3,4-<i>b</i>][1,3,4] thiadiazines

Abstract: ABSTRACT. Synthesis of [3,4-b] [1,3,4]thiadiazines from the condensation of 4-amino-6-methyl-3-thioxo-1,2,4-triazine-5(2H)-one (AMTTO) or 4-amino-1,4-dihydro-5-methyle-1,2,4-triazole-5-thione (AMTT) with phenacyl bromide in the presence of a catalytic amount of various heteropolyacids (HPAs) under refluxing conditions is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition, some attempts have been made to use sensitizers on the surface of photocatalyst or couple with other semiconductors in order to modify the physiochemical and electronic properties of photocatalyst (Marcì, García-López & Palmisano, 2014). Heteropoly acids (HPA), as green and eco-friendly catalysts, have been proposed as potential candidates to be used as surface modifiers of TiO 2 intended for photocatalytic degradation (Hakimi et al, 2014; Li, Vorontsov & Jing, 2015). The compound catalyst could eliminate the difficulties for recycling heteropoly acids and prevent the recombination of hole-electron pairs for both catalysts when heteropoly acids were carried on semiconductors such as TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some attempts have been made to use sensitizers on the surface of photocatalyst or couple with other semiconductors in order to modify the physiochemical and electronic properties of photocatalyst (Marcì, García-López & Palmisano, 2014). Heteropoly acids (HPA), as green and eco-friendly catalysts, have been proposed as potential candidates to be used as surface modifiers of TiO 2 intended for photocatalytic degradation (Hakimi et al, 2014; Li, Vorontsov & Jing, 2015). The compound catalyst could eliminate the difficulties for recycling heteropoly acids and prevent the recombination of hole-electron pairs for both catalysts when heteropoly acids were carried on semiconductors such as TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important advantages of heterogeneous catalysis over the homogeneous counterpart is the possibility of reusing the catalyst by simple filtration, without loss of activity [38][39][40]. We have studied the recyclability and reusability of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that H 3 PW 12 O 40 was used both in bulk and supported on silica as a catalyst in a reaction involving 2-aminobenzenethiols (1 mmol), acetylenic esters (1 mmol), malonate esters (3 mmol), and HPA (0.1 mmol or 100 mg of supported HPA) in i-PrOH (3 mL) at 50 • C for 7 h. In total, 11 compounds were obtained with yields of 81 to 92% (Scheme 40). Hakimi et al [129] studied the synthesis of [3,4- Gharib et al [132] presented the synthesis of polysubstituted quinolines in the presence of silica-supported Preyssler nanoparticles, H 14 [NaP 5 W 30 O 110 ]/SiO 2 (SiO 2 /P 5 W 30 ). A mixture of 2-aminoaryl ketone (1.0 mmol), α-methylene ketone (1 mmol) and heteropolyacid as catalyst (0.05 mmol) and water (1.0 mL) was refluxed for 2 h. In these conditions 29 substituted quinolines were obtained with yields of 89 to 96% (Scheme 44).…”
Section: Diazinesmentioning
confidence: 99%